Domain-general and domain-specific influences on emerging numerical cognition: contrasting uni-and bidirectional prediction models - Coolen, I; Merkley, R; Ansari, D; Dove, E; Dowker, A; Mills, A; Murphy, V; von Spreckelsen, M; Scerif, G (Elsevier, 2021)
Domain-general skills such as executive functions (EFs), and domain-specific skills such as non-symbolic number sense and symbolic understanding are often pitted against each other as predictors of emerging maths. Here we aimed to investigate early childhood relations between these foundational skills with a balanced, longitudinal design. One hundred and seventy 3- and 4-year-old-children were tested at two time points, 5 months apart, on four domain-general executive and five domain-specific numeracy tasks. A latent EF factor was a strong predictor of symbolic maths and of their growth. In addition, stronger symbolic maths at Time 1 was correlated with later stronger EF, but symbolic maths did not predict EF growth. Our findings provide novel insights into dynamic interplay between general and specific cognitive skills contributing to preschool maths.